"Finding Luther": Toward an Archaeology of the Reformer and the Earliest Reformation. Issue 4 (21st December 2017) - Nebelsick, Louis D.; Emmerling, Tomoko
Abstract : In view of Martin Luther's prominence as a person who changed the course of world history with his Reformation and given the abundance of historical sources on the reformer's life and work, the great extent to which archaeological discoveries of the last fifteen years have shed new and sometimes surprising light on the reformer's life might seem astonishing. The study at hand presents these new insights by introducing the results of archaeological excavations that took place on the premises of Martin Luther's parents' home in Mansfeld and in the garden of the Luther House in Wittenberg, which for more than thirty years was the home of the reformer. The discoveries made in both places allow new insights into the reformer's and his family's everyday life. They enrich, or even correct, our knowledge about these aspects with fascinating, new, and sometimes surprising facets. The majority of the archaeological finds took place prior to the exhibition "Finding Luther: Archaeologists on the Reformer's Trail" at the State Museum of Prehistory Halle (Saale) (2008/2009) and in the framework of the project "Luther Archaeology" at the State Office for Heritage Management and Archaeology of Saxony-Anhalt (2010–2015). These finds, as well as architectural, archival, and scientific investigations, shed new light on Martin Luther's family background and childhood, on the social status of his parents, as well as on his immediate living environment and the high living standard in his Wittenberg home. Taken together, these conditions reflect his social status as a respected professor of theology, protagonist of the Reformation, and member of the highest social class in Wittenberg. The last section of this study gives an insight into some selected results of further excavations that have been carried out throughout Wittenberg during the last few years. They make it possible to contextualize not only Luther's household but also the consequences of the Reformation within early modern Wittenberg.